(untitled) (Kronika Bydgoska, 2014)
In 1926-2014, there had been 71 finals of individual Men’s Polish Chess Championships, which were the most important national events. Chess players representing the Bydgoszcz clubs took part in 24 games of Polish Chess Championships, and these participations were analyzed in particular. A total of 15 players were classified, including Henryk Szapiel (1948-1953), Antoni Jurkiewicz (1949), Jerzy Bratoszewski (1955), Jerzy Pokojowczyk (1971, 1974, 1976-1982, 1984-1986), Andrzej Maciejewski (1973-1977, 1979-1980, 1982), Julian Gralka (1975-1979), Jan Rogalewicz (1975), Grzegorz Chrapkowski (1976), Wiesław Czerniakow (1976), Waldemar Hanasz (1976), Waldemar Jagodziński (1976), Włodzimierz Kruszyński (1977-1980), Adam Kujawski (1988), Robert Ciemniak (1993), and Łukasz Licznerski (2013). Top places had been won by only 3 out of the 15 mentioned chess players. Runner-up position in the Polish Championship had been won by Henryk Szapiel, Andrzej Maciejewski, and Jerzy Pokojowczyk; bronze medal winners included Jerzy Pokojowczyk and Włodzimierz Kruszyński. The list also included players who represented other regional associations or changed their place of residence. They included Sergiusz Czerniakow (1946, 1948), Alfred Czarnota (1946, 1950), Jerzy Lewi (1966, 1968-1969), Jerzy Konikowski (1977, 1979), Krzysztof Żołnierowicz (1984-1985, 1989-1990) and Andrzej Maciejewski (1992-1993). Jerzy Pokojowczyk reported the highest number of entries, participating in the championship twelve times. In the region (Pomerania, Bydgoszcz area, and combined areas of Bydgoszcz, Toruń, Włocławek and Kuyavia - Pomerania) there was a clear dominance of chess players from Bydgoszcz, including 15 out of 23 participants of Polish Chess Championship. The majority of chess players were members of the sports club KS “Łączność” (9 chess players - 29 entries). The author distinguished two separate periods of a visible presence of Bydgoszcz chess players in the finals of the Polish Championship. The first one took place in a period between the 1940s and 1950s, whereas the second one in the 1970s and 1980s. In the remaining years, lists of entries to the finals of the Polish Championship did not include chess players from Bydgoszcz.